2019 IEEE 5th International Forum on Research and Technology for Society and Industry (RTSI) 2019
DOI: 10.1109/rtsi.2019.8895574
|View full text |Cite
|
Sign up to set email alerts
|

I-READ 4.0: Internet-of-READers for an efficient asset management in large warehouses with high stock rotation index

Abstract: The I-READ 4.0 project represents an integrated and autonomous Cyber Physical System, for automatic management of very large warehouses with high-stock rotation index. Thanks to an internet of UHF-RFID readers, both fixed and mobile, it is possible to implement an efficient management of assets and forklifts operating in indoor scenario. The proposed solution can be employed independently on the warehouse sizes, the good types and the spatial resolution required for item localization by virtue of its low-cost,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The method has been conceived for industrial scenarios and account for specific position constraints. As an example, the issue related to pallet handling in warehouse applications [ 38 ] requires a pallet-placing uncertainty in the order of a few centimetres with a high level of confidence [ 39 ]. Hence, the main objective of the proposed approach is to robustly reduce to the maximum extent the localisation uncertainty and the vehicle trajectory estimation uncertainty to meet the industrial requirements.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…The method has been conceived for industrial scenarios and account for specific position constraints. As an example, the issue related to pallet handling in warehouse applications [ 38 ] requires a pallet-placing uncertainty in the order of a few centimetres with a high level of confidence [ 39 ]. Hence, the main objective of the proposed approach is to robustly reduce to the maximum extent the localisation uncertainty and the vehicle trajectory estimation uncertainty to meet the industrial requirements.…”
Section: Related Workmentioning
confidence: 99%
“…In [36], Magnago et al showed that the localisation problem can be theoretically solved locally, i.e., the a priori starting position estimate is closer to the initial actual position of the agent, and considering unicycle-like robots, which are a commonplace in industrial environments for warehouse management or for transportation in production lines. Successively, it has been shown that the problem can be actually solved also globally [37], provided that some mild assumptions on the uncertainties are satisfied. Given that the localisation problem is well-posed when RFID tags are used and fused with odometry for unicycle-like vehicles [37], the authors of this paper recently proposed in [24] a solution for industrial IoT applications based on an Extended Kalman Filter.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The system consists of a network of RFID readers in the Ultra-High-Frequency (UHF) operating band, which are able to automatically collect data from the warehouse pallets equipped with UHF-RFID tags and stored within the tissue-paper warehouse of the Sofidel Italian Company in Porcari, Lucca. Firstly presented in [ 12 ], the I-READ 4.0 system consists of two main technological elements: UHF-RFID Smart Gate and UHF-RFID Smart Forklift. The Smart Gates use fixed readers able to detect forklifts/pallets entering or exiting from areas of interest.…”
Section: Introductionmentioning
confidence: 99%